Association of Nausea and Vomiting in Pregnancy With Prenatal Marijuana Use - Young-Wolff, Kelly C. (JAMA Intern Med, 2018)
This observational study of a health care system population assessed whether prenatal marijuana use is elevated among women with nausea and vomiting in pregnancy who underwent universal screening for marijuana use.